A zero-dimensional model for atmospheric non-thermal plasma CO2 hydrogenation: insights into the reaction mechanism. (1st August 2022) - Chen, Yeli; Peng, Yi; Qian, Muyang; Liu, Sanqiu; Zhang, Jialiang; Wang, Dezhen
Abstract: Recently, plasma CO2 hydrogenation to generate valuable products (e.g. CO and CH4, hydrocarbons and oxygenates) has attracted more and more attention. The conversion of carbon dioxide (CO2 ) and hydrogen (H2 ) in an atmospheric non-thermal plasma was investigated by a zero-dimensional plasma kinetic model. This paper focuses on the effect of different feed gas composition ratios (H2 /CO2 volume ratio) on the plasma CO2 hydrogenation reaction mechanisms. It is found that H2 addition in plasma not only promotes CO2 dissociation but also changes the plasma chemistry, which seems to significantly enhance the electron density and temperature. Besides, larger H2 content in the H2 /CO2 mixture is beneficial to obtaining a higher number density of methanol, which is in good agreement with published experimental data. The temporal distributions of abundant radicals, ions and molecule densities are determined under a series of initial hydrogen content. Conversions of inlet H2 /CO2 and selections toward CO and CH4 are calculated and presented. The primary reaction channels related to the production and destruction of CO, H, CH2 O, CH3 OH, CH4 and H2 O are determined. Finally, the underlying overall reaction mechanisms regarding the plasma CO2 hydrogenation are analyzed in detail by the chemical reaction flow chart.